Experience of surgical treatment of combat pancreatic trauma - Е.М. Хорошун; І.П. Хоменко; С.А. Шипілов; В.В. Макаров; В.В. Негодуйко; О.Г. Петюнін (Медицина неотложных состояний, 2024)
Background. Pancreatic injuries is a complex challenge for trauma surgeons, especially if combat, due to the presence of combined injuries and complications. The aim: to provide a structure, peculiarities of diagnosis and treatment of combat pancreatic trauma. Materials and methods. A retrospective analysis was done of medical records of 58 inpatients who sustained combat pancreatic trauma during the war in Ukraine. Their average age was 37.4 ± 3.6 years (range 21–60 years). The mechanism of combat injury included gunshot wounds (87.9 %), explosive (10.3 %) and closed injuries (1.7 %). All the wounded underwent laboratory and instrumental investigations. Results. According to the nature of the combat injury, pancreatic injuries were categorised into gunshot shrapnel wounds — 50 (86.2 %), gunshot bullet wounds — 1 (1.7 %), explosive trauma — 6 (10.3 %), and closed combat trauma — 1 (1.7 %) case. Distribution by location of pancreatic injury: tail — 38 (65.5 %), head — 11 (19 %), body — 5 (8.6 %), body and tail — 2 (3.4 %), head and tail — 2 (3.4 %) cases. The following methods of surgical intervention were used: damage control surgery (DCS) — 51 (87.9 %) cases, one-stage surgery — 7 (12.1 %) cases. Distribution by the type of surgical intervention for pancreatic injury: drainage of the parapancreatic space — 45 (77.6 %), pancreatorrhaphy — 4 (6.9 %), distal pancreatosplenectomy — 3 (5.2 %), removal of foreign bodies (metal fragments) — 3 (5.2 %), distal resection of the pancreas with spleen preservation — 1 (1.7 %), pancreatoduodenectomy — 1 (1.7 %), subtotal resection of the body and tail of the pancreas with splenectomy — 1 (1.7 %) case. Common complications (n = 42): peritonitis — 9 (21.4 %), acute surgical sepsis — 8 (19 %), acute renal failure — 7 (16.7 %), multiple organ failure syndrome — 7 (16.7 %), pneumonia — 6 (14.3 %), bleeding — 4 (9.5 %), pulmonary embolism — 1 (2.4 %). Organ-specific complications (n = 28) were as follows: acute pancreatitis — 21 (75 %), pancreatic fistula — 4 (14.3 %), pseudocysts — 2 (7.1 %), abscess — 1 (3.6 %) case. Treatment outcomes: 33 patients (56.9 %) were transferred to the next stage of treatment, 19 (32.8 %) died, and 6 (10.3 %) were discharged with a definite outcome. Mortality rate: 5 (26.3 %) died in the first 3 days, 14 (73.7 %) cases died in the period from 4 to 15 days. Conclusions. The incidence of combat pancreatic trauma among abdominal wounds is 8.7 %. Surgical treatment for combat pancreatic trauma using the DCS is performed in 87.9 % of cases, and in the volume of a single-stage operation, in 12.1 %. The DCS leads to a reduction in the incidence of complications. The overall complication rate for combat pancreatic trauma is 72.4 %, and the incidence of organ-specific complications is 48.3 %. Mortality from pancreatic injuries is 32.8 %. Combat trauma to the head of the pancreas was mainly treated with closed drainage. Distal injuries were treated by resection or drainage.